Hadith #3467 - Sunan Abi Dawud - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Ziyad bin Khaythama al-Ja'fi زياد بن خيثمة الجعفي (Sunan Abi Dawud)
A man paid in advance for a palm-tree. It did not bear fruit that year. They brought their case for decision to the Prophet (ﷺ). He said: for which do you make his property lawful? He then said: Do not pay in advance for a palm-tree till they (the fruits) were clearly in good condition.
Grade: Da'if

Hadith #3925 - Sunan Abi Dawud - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abu Salma al-Himsi Suliaman bin Saleem أبو سلمة الحمصي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) took a man who was suffering from tubercular leprosy by the hand; he then put it along with his own hand in the dish and said: Eat with confidence in Allah and trust in Him.
Grade: Da'if